Parents' approaches to sexuality education of their adolescent boys: a qualitative study in Ahvaz, Iran - Zahra Rouhparvar; Mojgan Javadnoori; Shadab Shahali (BMC, 2022)
Plain language summary Children's sexuality education has an important role in adolescent sexual behaviors and health. However, it is one of the most challenging dimensions of education in families, especially in Muslim communities experiencing the transition to modernity. There is little information about sexuality education of adolescent boys in Iran. In this study we aimed to explore parents' experiences and perceptions of communicating sexuality education with their sons. Data were collected through individual interview with 11 parents and group discussion with 8 fathers and 8 mothers who had sons aged 10-19, living in Ahvaz, in south west of Iran. We summarized and categorized parents' approaches to sexuality education in categories including: Extreme monitoring and restricting; abstinence as the main content of sexuality education; struggling to establish peace and achieve tolerance; criticizing the cultural taboos; hoping for spontaneous learning; and uncertainty and confusion. Parents' approaches to sexuality education ranged from a restrictive traditional manner to some degree of modern conduct. Findings imply that parents are facing challenges regarding sexuality education: uncertainty about the necessity of it, and confusion between religious teachings and modernity. Abstinence is still a central assumption and pre-marital sex is off-limits in their sexuality education. They hoped that they could enhance the children's adherence to family's values regarding sexuality, by establishing a peaceful relationship with them. These findings provide evidence for culturally-appropriate educational programs for parents to improve their skills and knowledge about sexuality education. These findings highlighted the fact that Iranian parents are experiencing a "Transition from tradition to modernity".